2015
DOI: 10.15430/jcp.2015.20.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-disrupting Chemicals: Review of Toxicological Mechanisms Using Molecular Pathway Analysis

Abstract: Endocrine disruptors are known to cause harmful effects to human through various exposure routes. These chemicals mainly appear to interfere with the endocrine or hormone systems. As importantly, numerous studies have demonstrated that the accumulation of endocrine disruptors can induce fatal disorders including obesity and cancer. Using diverse biological tools, the potential molecular mechanisms related with these diseases by exposure of endocrine disruptors. Recently, pathway analysis, a bioinformatics tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 94 publications
(99 reference statements)
1
81
0
5
Order By: Relevance
“…Within the range of 0.02-21 ng/ml (0.8-84nM) it has been detected in human urine samples originating from seven Asian countries and the USA (Liao et al 2012a) in 81% of analyzed samples. In the following study the presence of BPS in urine was demonstrated in residents living near a manufacturing plant in south China in a concentration of 0.029 ng/ml (Yang et al 2015).…”
Section: The Advent Of Bpsmentioning
confidence: 83%
See 1 more Smart Citation
“…Within the range of 0.02-21 ng/ml (0.8-84nM) it has been detected in human urine samples originating from seven Asian countries and the USA (Liao et al 2012a) in 81% of analyzed samples. In the following study the presence of BPS in urine was demonstrated in residents living near a manufacturing plant in south China in a concentration of 0.029 ng/ml (Yang et al 2015).…”
Section: The Advent Of Bpsmentioning
confidence: 83%
“…BPA is released into the environment either directly from chemical, plastic coating, and staining manufacturers, from paper or material recycling companies, foundries which use BPA in casting sand, or indirectly leaching from plastic, paper, and waste in landfills (Yang et al 2015). BPA passes into foodstuffs or water directly from the lining of food and beverage cans, where it is used as an ingredient in the plastic used to protect the food from direct contact with the can (Goodson et al 2002;Vandenberg et al 2009).…”
Section: Bisphenol Amentioning
confidence: 99%
“…The result of semen evaluation herein confirmed that the administration of MEPD to cadmium exposed rabbit bucks increased the number of spermatogonia which resulted in the significant (p < 0.05) increase in sperm concentration. This may have been due to the stimulation of androgen biosynthesis, possibly by regulating progesterone synthesis and metabolism which may have been altered through direct interaction of cadmium with deoxyribonucleic acid (DNA) and competitive inhibition of essential enzymes (Yang, Kim, Weon, & Seo, 2015). Also by the initiation of FSH synthesis (Mehraban et al, 2014) which perhaps increased the proportion of cells passing through meiosis and spermatogenesis thus increasing semen concentration and total sperm per ejaculate.…”
Section: Resultsmentioning
confidence: 99%
“…Fruits and vegetable represent also one of the main human exposure sources to organochlorine pesticides, dangerous compounds related with increased risk of developing several hormonally-related cancers (Lerro et al, 2015). The increasing interest in the determination of these chemicals is due to consolidated evidences underlining their role in the pathogenesis of several diseases such as cancer, obesity (Yang et al, 2015), diabetes (Chevalier and Fenichel, 2015) and reproductive pathologies (Kumar and Holt, 2015). EDCs exposure is particularly dangerous during childhood.…”
Section: Synthetic Xenoestrogens: Endocrine Disrupting Chemicals (mentioning
confidence: 99%